Successful frameless radiosurgery for glossopharyngeal neuralgia — Case report - Chua, Evan (J Radiosurg SBRT, 2020)
Idiopathic glossopharyngeal neuralgia (GPN) is a rare disorder of the ninth cranial nerve characterized by severe paroxysmal pain affecting the ear, tongue and throat. Frame-based radiosurgery (SRS) has been shown to be an effective option. We report the first successful pain alleviation by frameless SRS in a GPN patient that failed both medical and surgical interventions.